Congenital cytomegalovirus in Sub-Saharan Africa-a narrative review with practice recommendations - Helen Payne; Helen Payne; Shaun Barnabas (Frontiers Media S.A., 2024)
Cytomegalovirus (CMV) is the most common cause of congenital infection internationally, occurring in 0.67% of births, and increasingly recognised as a major public health burden due to the potential for long-term neurodevelopmental and hearing impairment. This burden includes estimates of 10% of childhood cerebral palsy and up to 25% of childhood deafness. In Sub-Saharan Africa, where CMV-seroprevalence is almost ubiquitous, prevalence of congenital CMV (cCMV) is higher than the global average, and yet there is a dearth of research and initiatives to improve recognition, diagnosis and treatment. This narrative review outlines the epidemiology and clinical presentation of cCMV, discusses issues of case identification and treatment in Sub-Saharan Africa, and recommends a framework of strategies to address these challenges. Considering the significant burden of cCMV disease in this setting, it is undoubtably time we embark upon improving diagnosis and care for these infants.